Investigation of solvent sublation of cobalt ions from water solutions - Obushenko, Tetjana; Tolstopalova, Nataliia; Baranuk, Nadiya (Technology audit and production reserves, 2018)
The object of research is solvent sublation in the cobalt - sodium dodecyl sulphate system. The study of solvent sublation of wastewater from heavy metal ions is small and fragmented and unsystematic. Therefore, the study of the solvent sublation process, as a method of purification of waste water from heavy metals on the example of cobalt ions (II) is promising. In this work, model cobalt aqueous solutions with a concentration of 20 mg/dm3 were investigated using anionic surfactant, sodium dodecyl sulfate and isoamyl alcohol as the organic phase. The following rational process conditions were obtained: pH 10 molar ratio Со2+:surfactant = 1:2, air consumption – 45 cm3/min, temperature – 20 °С, extractant volume (isoamyl alcohol) – 10 cm3, process duration – 20 min. Under these conditions, the extraction degree of cobalt ions in isoamyl alcohol was 85 %. The process is described by a first order kinetic equation. Process rate constants are calculated. The importance of research is emphasized by the fact that solvent sublation has a number of features and advantages. In particular, the possibility of multiple concentration of pollutant ions in small volumes of organic solvent and the possibility of its further regeneration. It uses a much smaller amount of organic solvent and the process is not limited by the distribution constant (as compared to the extraction method). Solvent sublation is also characterized by the absence of foam (as compared with the flotation method) and the absence of large amounts of wet sediment (as compared with the reagent method). The proposed method provides a sufficient level of wastewater purification from metal ions, and can also be applied in local wastewater purification systems with subsequent return of water to the process. This will reduce the costs of water consumption, wastewater discharges into water bodies, as well as limit the release of harmful substances into the environment. In addition, the characteristics of solvent sublation can regenerate the extractant and surfactant.